Analyzing the Efficacy of Restorative Justice Practices in Criminal Law - HM, Makkah; Utama, Andrew Shandy; Guna, Bucky Wibawa Karya; Kurniawan, Andri; Nugraha, Aat Ruchiat; Suhardy, Suhardy; Sarnoto, Ahmad Zain; Triantho, Alex Irawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the effectiveness of restorative justice practices in the context of criminal law. Restorative justice is an alternative approach that focuses on restoring relationships between perpetrators, victims, and society through dialogue and out-of-court settlements. With the growing idea that traditional criminal justice systems are often more repressive than rehabilitative, restorative justice offers a new paradigm that emphasizes perpetrator responsibility, victim recovery, and active community involvement. This study uses case study methods and literature reviews to evaluate the extent to which restorative justice practices are able to achieve their main goals, namely reducing recidivism, recovering victims, and reintegrating perpetrators. The results show that, while restorative justice is effective in some contexts, its implementation is often hampered by a lack of understanding, a supportive legal framework, and resistance from traditional legal systems. In conclusion, although restorative justice has great potential in improving the weaknesses of the conventional criminal justice system, further development is needed in policy and application to ensure its success more broadly.